1999
DOI: 10.1007/s004150050483
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis: interobserver agreement in reporting active lesions on serial brain MRI using conventional spin echo, fast spin echo, fast fluid-attenuated inversion recovery and post-contrast T1-weighted images

Abstract: Previous studies have addressed the question of the precision in assessing multiple sclerosis (MS) activity by counting enhancing lesions on gadolinium enhanced brain magnetic resonance imaging (MRI). However, counting the active lesions on serial unenhanced MRI obtained by various pulse sequences has not been yet considered. We compared the interobserver levels of agreement in reporting active MS lesions on serial enhanced and unenhanced MRI to assess whether the use of various unenhanced techniques may chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…By contrast, the IP-trained raters maintained a substantial level of agreement on DIS from baseline to the last follow-up scan. The levels of agreement found for new T2 and new enhancing lesions in the current study are similar to those previously reported for experienced raters [9,15], although some studies showed even better results [16]. The resulting final agreement on DIT was moderate in both groups and higher than reported by the interobserver study from Zipoli et al [10], probably due to better performance by radiologists than neurologists when identifying new T2 or new enhancing lesions.…”
Section: Discussionsupporting
confidence: 88%
“…By contrast, the IP-trained raters maintained a substantial level of agreement on DIS from baseline to the last follow-up scan. The levels of agreement found for new T2 and new enhancing lesions in the current study are similar to those previously reported for experienced raters [9,15], although some studies showed even better results [16]. The resulting final agreement on DIT was moderate in both groups and higher than reported by the interobserver study from Zipoli et al [10], probably due to better performance by radiologists than neurologists when identifying new T2 or new enhancing lesions.…”
Section: Discussionsupporting
confidence: 88%
“…The presence and number of gadolinium enhanced lesions were assessed by an experienced observer following published guidelines. 7 Differences in β endorphin concentrations were analysed by analysis of variance, followed by post hoc Bonferroni corrected t test. Correlations were evaluated with the Pearson product moment correlation.…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes this is called the test-retest performance. It has been measured for many parameters, for example spectroscopy (Charles et al, 1996;Marshall et al, 1996;Simmons et al, 1998;Bartha et al, 2000;Chard et al, 2002), dynamic Gd imaging (Buckley, 2002;Galbraith et al, 2002;Padhani et al, 2002), fMRI (Tegeler et al, 1999;Loubinoux et al, 2001), tissue volume (Fox and Freeborough, 1997;Lemieux et al, 2000;Cardenas et al, 2001;Gasperini et al, 2001), lesion volume (Grimaud et al, 1996;Vaidyanathan et al, 1997;Rovaris et al, 1998;Filippi et al, 1998b), lesion counting (Rovaris et al, 1999;Wei et al, 2002), spinal cord cross-sectional area (Leary et al, 1999) and clinical scores (Cohen et al, 2000). Its value depends on the method used to measure the parameter, and is often very sensitive to the precise details of the data collection procedure (such as patient positioning and pre-scan procedure) and data analysis (particularly ROI placement).…”
Section: Precisionmentioning
confidence: 99%